Anticariogenic potential of Potentilla fulgens extract and its chemical constituents - Alka Choudhary; Umesh Bihade; Amit Kumar Mittal; Anupam Chatterjee; Uttam Chand Banerjee; Inder Pal Singh (International Journal of Phytomedicine, 2017)
Streptococci and Lactobacilli are the most common bacteria causing dental caries. Potentilla fuglens, native of north-east India is used by tribal people to cure teeth and gum problems. Based on its ethomedical use, its anticariogenic potential was evaluated. The crude methanol extract was found to have good anticariogenic potential. Epigallocatechingallate (4) was found to the most effective inhibitor against the tested bacterial strains. Epiafzelechin (4β→8) epicatechin (8) also demonstrated comparatively better activity than other dimeric compounds (MIC of 1.56, 3.12 and 3.12 μg/mL against Streptococcus mutans, Lactobacillus acidophilus and Lactobacillus rhamnosus, respectively). Time-kill studies and biofilm formation inhibition assays showed molecule 8 to be comparable to compound 4 in terms of antibacterial action. The results suggest that these compounds and Potentilla extracts could be employed as natural antibacterial agents in oral health care products.